Early childhood learning and development - Moreno Zavaleta, María Teresa (2020)
During early education, we concentrate our efforts to teach the child what he has to learn, and we do not look at what the child can learn for himself, children learn through interaction with adults, with their peers, with objects, to through the game, and learning projects. From the birth of a child, he can learn and develop. Adult caregivers and the preschooler teacher play a crucial role, knowing the child in action to offer a safe, enriched, and suitable environment. This article presents an analysis of the concepts of care/ education and theories of learning and development through different theoretical frameworks. It also makes them know how the teacher can use simple tools in class to promote children's education through projects. To the extent that adult caregivers, including the teacher, identify the needs and interests of children and know how the child learns according to different theories of knowledge and child development, they can contribute to improving children's learning in the context school or family and community environment.